Generalized connectedness in fuzzy bitopological spaces - Alharbi, A. A.; Kilicman, A. (Natural Sciences Publishing, 2023)
The primary objective of this research is to study generalized connectedness ideas in the domain of fuzzy bitopological spaces. Additionally, it presents basic theorems to figuring out how they relate to one another, and to explore some of the primary characteristics of connectedness structures. Finally, we looked at the idea of disconnection as well as all of its fundamental theories and characteristics.